From a ‘Ruthenian’ to a ‘Noble Lithuanian’: Shifts in the Sixteenth-Century Historical Narrative of the Grand Duchy of Lithuania - Gudmantas, Kęstutis (Senoji Lietuvos literatūra, 2024)
The article discusses the shifts in the attitude towards the Orthodox believers and Ruthenians in the sixteenth-century historical and polemical writings and epistolary works of the Grand Duchy of Lithuania. It starts with an analysis of the conversion of pagan Lithuanian dukes to Orthodoxy as described in the chronicles of Lithuania, which is followed by a review of the letters of Chancellor Albertas Goštautas (Olbracht Gasztołd, †1539) and the struggle against the group of Hetman Konstantinas Ostrogiškis (Konstanty Ostrogski) that is reflected in those letters. The study concludes with an analysis of texts by Augustinus Rotundus, Maciej Stryjkowski, and other authors from the second half of the sixteenth century. In these texts, the representatives of the Ruthenian elite of the Grand Duchy of Lithuania – the Chodkevičius (Chodkiewicz), the Valavičius (Wołłowicz) – are already considered to be ‘noble Lithuanians’.